Pendampingan Penyusunan Karya Tulis bagi Siswa MA Ma’arif NU Durensewu Pandaan Pasuruan - Mochamad Hasyim; Siti Anifah; Nurul Hidayati; Saiful Umar; Misbahul Munir (LPPM Universitas Yudharta Pasuruan, 2021)
Community service program in the form of mentoring the preparation of this writing work begins with a workshop. This activity involves cooperation between the Arabic Education Study Program of Yudharta Pasuruan University and MA Ma'arif NU Durensewu Pandaan Pasuruan. Thematic learning preparation assistance at MA Ma'arif NU Durensewu Pandaan Pasuruan is carried out by service-learning methods and technical approaches through 4 stages, namely (1) writing preparation workshop, (2) assignment, (3) coaching clinic, and (4) evaluation and reflection. Based on the results of the devotion that has been done, it can be concluded that the assistance activities of writing on thematic learning at MA Ma'arif NU Durensewu Pandaan Pasuruan with service learning methods are very effective with a systematic approach with workshop stages, assignments, coaching clinics, evaluation and reflection. Comparison of assessment of the results of the assignment of the preparation of written works before and after mentoring is carried out shows satisfactory results. Before mentoring the average student's grade is 54, very less than the KKM standard <70. As for the assistance of the average student, the value is 73-78, very satisfactory more than the KKM standard >70. There are technical obstacles in the implementation of mentoring activities, namely the limited equipment available in the form of computers, so the devotional team must find an alternative laptop for each group that has been divided to do the task of preparing writing well and correctly.